Quality of service ontology languages for web services discovery: an overview and limitations - Zeshan, Furkh (2013)
Web services discovery, ranking and selection based on QoS parameters is remained a hot topic for research since the start of the semantic web. Quality of service (QoS) plays an important role to resolve the issue of best service among the functional similar services. Semantic web relies on the ontologies for providing metadata schema and the vocabulary of concepts used in semantic annotation; resulting improved accuracy of web search. This is why; the success of semantic web depends on the proliferation of ontologies. Depending on the nature of the application, different companies may use different ontology languages and QoS models for web services selection which lead to the issue of heterogeneity. In this paper we have presented ontology evaluation criteria that if satisfied, can solve the problem of heterogeneity and interoperability. Moreover, ontology developers may also use these criteria to evaluate their developed ontology for the refinements. We have evaluated different ontologies in-order to know their strengths and limitations along with the new research directions.